Progress Report on Crisis Resolution. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Describes progress in the inclusion of CACs in international sovereign bonds. Provides an update of efforts to broaden the consensus on the Principles. Reports on developments in recent sovereign debt restructuring cases. Discusses progress in the Evian Approach and other Paris Club issues. Provides a summary of the aforementioned paper on the determinants and prospects for regaining market access.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet